Pengaruh Relaksasi Nafas Dalam Terhadap Pola Tidur Lansia di BPSTW Yogyakarta Unit Budhi Luhur - Yuda Prawinata; Thomas Aquino Erjinyuare Amigo; Ririn Wahyu Widayati (Peneliti.net, 2019)
This aim of this study is to find out deep breathing relaxation technique can affect on the elderly sleep patterns at BPSTW of Budhi Luhur Unit Yogyakarta. The reseach used a quantitative research method. It was quasi experimental research using a pre-test and post-test with a non-equivalent control group design. A convinience sampling technique was used to collect data from as many as 20 elderly people in each group. The wilcoxon analysis was applied to the intervention and control groups before and after practicing the deep breathing exercise. Meanwhile, the Mann-Whitney test was applied to the intervention and control groups after practicing the deep breathing exercise. The results indicate that the sleep patterns in the control group before and after practicing the deep breathing exercise show a p-value of 0.296, while the intervention group shows a p-value of 0.000. the bivariate analysis on the intervention and control groups after practicing the deep breathing relaxation techniques shows a p-value of 0.000. since the results indicate a p-value of less than 0.005 (p<0.05), it is concluded that there is a difference in the sleep patterns scores of the groups with the deep breathing relaxation treatment and the groups without the deep breathing relaxation treatment.